Facile green synthesis of Ag/AgCl nanoparticles derived from Chara algae extract and evaluating their antibacterial activity and synergistic effect with antibiotics. Issue 4 (August 2021) - Hassan, Khalil T.; Ibraheem, Ibraheem J.; Hassan, Omar M.; Obaid, A.S.; Ali, Hameed Hussein; Salih, Thaer Abdulqader; Kadhim, Mohammed S.
Abstract: Here, we present a pathway for the green synthesis of Ag/AgCl nanoparticles derived from freshwater Chara vulgaris algae. The formation of Ag/AgCl NPs is confirmed by XRD, UV–Vis spectroscopy, and SEM techniques. The volume with an aqueous extract of Chara vulgaris : AgNO3 ratio 3:1 possessed optimal synthesised Ag/AgCl NPs. A plasmon absorbance peak, at 395 nm was observed in the UV–vis spectrum. XRD patterns confirmed the highly crystalline FCC structure of Ag/AgCl NPs. SEM imaging of Ag/AgCl NPs indicated nanoparticles of size 16.99 ± 0.3 nm. The antibacterial activity of Ag/AgCl NPs was evaluated against Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, and Pseudomonas aeruginosa . Combining Ag/AgCl NPs with antibiotics causes growth inhibition of both Gram-positive and Gram-negative bacteria. The fractional inhibitory concentration index (FICI) is used to evaluate the synergistic antimicrobial effect of combining nanoparticles with antibiotics. The combinations of Ag/AgCl NPs with Gentamicin, Erythromycin and Vancomycin show a partial synergistic activity against E. coli, K. pneumoniae and P. aeruginosa, respectively. The combination of Ag/AgCl NPs with antibiotics could potentially prohibit the development of resistant bacteria against antibiotics. Graphical Abstract: ga1 Highlights: Silver and silver chloride nanoparticles were biosynthesised using Chara algae extract. The antibacterial activity was evaluated against the isolated pathogenic bacteria. The synergistic effect of combined nanoparticles with selected antibiotics was investigated.